P710 Changes of gut microbiome after anti-TNF-α therapy and the prediction of clinical remission in patients with active ulcerative colitis. (30th January 2023) - Shin Shin, S; Oh, H N; Moon, J M; Joo, H J; Sul, W J; Choi, C H
Abstract: Background: The aims of this study are to explore the changes of gut microbiome after anti-TNF-α therapy (adalimumab; ADA) and to identify biomarkers to predict clinical remission to ADA in patients with active ulcerative colitis (UC). Methods: Fecal samples were taken before (baseline) and after ADA administration at weeks 8 and 56 in patients with active UC. Fecal bacterial taxonomic composition and diversity were investigated by 16S sequencing and analyzed by divisive amplicon denoising algorithm version 2 (DADA2) at the level of amplicon sequence variant (ASV). The table was imported into R 4.0.2 to analyze for richness, diversity, heatmap and ordination plot . The linear discriminant analysis effect size (LEfSe) was used for statistical analysis. Clinical remission was assessed using the Mayo score. Results: 260 fecal samples from 146 patients with UC administering ADA and 40 fecal samples of healthy controls (HC) were analyzed. The mean age of the participants was 44 ±14.8 years, and 60.7% were male (patients 64.9%, healthy control 42.5%). Overall communities (β-diversity) of gut microbiota in HC clearly differed from those before, after 8 weeks, and after 56 weeks of ADA treatment in patients with UC regardless of remission. The compositions of microbiota were affected by the disease severity and extent. ADA treatment significantly reduced the dissimilarity among samples in remitters at both 8 and 56 weeks, which were not observed in non-remitters. In remitters, the abundance of genus Staphylococcus was significantly decreased and genera Bifidobacterium and Dorea were significantly increased during ADA treatment period. The baseline samples of remitter at week 8 showed a higher abundance of 40 ASVs, including Sporosarcina (ASV2803), Bacteroides sp. (ASV1298, ASV1490), and Enterobacter (ASV9330, ASV9332) compared to baseline of non-remitters. Given that the 48 ASVs increased or decreased in baseline samples of remitters at week 8, the best log ratio of average relative abundance of increased ASVs/decreased ASVs to predict remission for ADA treatment was 0.07459, with 72.4% sensitivity and 84.3% specificity on the receiver operating curve (area under the curve, 0.855). Conclusion: The composition of gut microbiota varies depending on the status of the disease and the effectiveness of the ADA treatment. Relative abundance of s fecal bacteria before treatment can be a biomarker for predicting efficacy of ADA in patients with UC.